Enhancing Fish Quality and Yield: An Automated Aquaculture Monitoring System - Chaoxiang; Ping (Advances in Aquaculture and Fisheries Management, 2025)
A The market's declining natural fish stocks are the main cause of the increased interest in the fish farming sector. However, depending on the species being raised, intensive aquaculture systems—which raise fish in artificial tanks and cages—can result in problems including low-quality fish and higher death rates. This research suggests a fish quality monitoring system with automatic correction to handle these problems and optimize productivity. Temperature, water level, pH level, and other vital water quality factors that are necessary for fish growth are the major emphasis of the system. The system consists of a web-based application for data gathering and monitoring, as well as an Arduino with sensors attached. To keep these parameters at ideal levels for fish development, correction devices like a water pump, valve, and aquarium heater are incorporated into the system. Two fish monitoring settings were compared, one using the suggested controlled system and the other using a conventional setup, in order to evaluate the system's effectiveness and dependability. Comparing the controlled system to the conventional setup, the results show that it enhanced product quality, cut fish mortality rates, lessened stress on fish farmers, and boosted efficiency.